Systematic reviews of ten pharmaceutical pricing policies - a research protocol - David Tordrup; Hendrika A. van den Ham; Julie Glanville; Aukje K. Mantel-Teeuwisse (Taylor & Francis Group, 2020)
Background High prices of pharmaceutical products are an increasing challenge in high- and low-income countries. Governments in many countries have implemented pricing policies to ensure affordability of medicines to patients and healthcare systems. The World Health Organization published in 2015 the Guideline on Country Pharmaceutical Pricing Policies, which was based on a series of evidence reviews in the preceding years. As part of the ongoing update of this guideline, we present a protocol for 10 systematic literature reviews on pharmaceutical pricing policies to be covered by the updated guideline. Methods The systematic literature reviews will be undertaken according to the principles embodied in the Cochrane Handbook and Centre for Reviews and Dissemination. The interventions studied are pharmaceutical pricing policies implemented by public institutions or a group of purchasing organizations/individuals (e.g. health services). Studies reporting price, volume, availability and/or affordability as the primary outcomes will be eligible for inclusion. Studies in any country or jurisdiction, in any language and in any setting published in 2004 or later are eligible. Eligible study designs are randomized and non-randomized trials, and observational studies including cohort studies, panel data analyses, comparative time series design (including interrupted time-series and repeated measures studies), and controlled before-after studies. A list of 21 databases of peer-reviewed and grey literature will be searched, along with supplementary searches of relevant national and international organizational and governmental websites. Risk of bias will be assessed according to the Cochrane Effective Practice and Organisation of Care (EPOC) guidelines. A summary table according to the EPOC Worksheets for preparing a Summary of Findings table (SoF) using GRADE will be provided. Discussion The results of the review will be used as part of the update of the WHO Guideline on Country Pharmaceutical Pricing Policies. The current protocol may serve as an example for performing systematic literature reviews to inform policy makers.